Negativna povratna zveza - Dolenšek, Janez (Medicinski razgledi, 2004)
Negative feedback is one of the most difficult topics in physiology, possibly because descriptive thinking is useless. Instead, to analyse single constituents quantitatively or semiquantitatively, causal thinking is mandatory. By using analogic simulation, the author tries to show the basic properties of negative feedback. The characteristics of an ideal negative feedback - operating without any appreciable delay - are shown.Then the characieristics of a real negative feedback - including a distinct delay - areshown. Finally, the role of negative feedback in analogue simulation of pulmonary ventilation is described.
Keywords: Apneja; Hemostasis; Hemostaza; Blood Pressure; Krvni pritisk; Pulmonary Ventilation; Apnea; Pljučna ventilacija; Povratna zveza; Feedback; Computer Simulation; Računalniška simulacija; fiziologija; homeostaza